A practical approach for the strength evaluation of RC columns reinforced with RC jackets. (15th February 2015) - Minafò, Giovanni
Highlights: RC jacketed sections subjected to axial load and bending moment are considered. Constitutive laws of confined concrete and steel are calculated. The equivalent stress block parameters for concrete are determined. A simplified approach for calculating the interaction domain is proposed. Comparisons with numerical analyses and experimental results show good accordance. Abstract: Reinforced concrete (RC) jacketing is nowadays one of the most common techniques adopted for seismic retrofitting of existing RC columns. It is used to increase load-carrying capacity and ductility of weak existing members by means of a simple and cheap method. The structural efficiency is related to two main effects: – the enlargement of the transverse cross section; – the confinement action provided by the external jacket to the inner core. Several theoretical and experimental studies were addressed in the past to investigate on how it is possible to calculate the strength enhancement due to these effects and to highlight the main key parameters influencing the structural behavior of jacketed columns. Most of theoretical studies analyzed members subjected to axial compression while the case of axial force and bending moment was adapted only with complex formulations based on numerical approaches, which require the use of a suitable algorithm (e.g. non-linear finite element analyses, sectional fiber models). This paper presents a simplified approach, able to calculate the strength domains for jacketed columns subjected to axial force and uniaxial bending moment. The model takes into account the effects of confinement with proper stress-block parameters, the latter adapted for confined concrete, and of the composite action of jacket and core; buckling of longitudinal bars is considered and discussed with an appropriate stress–strain law for steel in compression. Results are compared with numerical analyses carried-out with the fiber model approach implemented in a commercial software (SAP2000), showing the accuracy of proposed method. Comparisons are also made with experimental results available in the literature in order to validate the model. Finally parametric considerations are made on the basis of adopted model, useful for design/verification purposes.